FUNCTIONAL OUTCOMES OF CONSERVATIVE VERSUS SURGICAL TREATMENT IN DISTAL RADIUS FRACTURES: A PROSPECTIVE INTERVENTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Distal radius fractures (DRFs) are among the most common orthopaedic injuries, with management strategies ranging from closed reduction and casting to open reduction and internal fixation (ORIF). Optimal management remains debated, particularly in mixed-age populations with varying fracture morphologies. Aim: To compare functional outcomes of conservative and surgical interventions in the management of distal radius fractures. Methods: This prospective interventional study was conducted in the Department of Orthopaedics, Rohilkhand Medical College & Hospital, Bareilly, over one year. Seventy-four patients aged ≥18 years with extra- or intra-articular distal radius fractures were allocated to two groups of 37 each. Group A received closed reduction and below-elbow plaster cast immobilization for six weeks, while Group B underwent ORIF with a volar locking plate or Joshi’s External Stabilising System (JESS) fixator. Patients were followed at 2, 6, 8 and 24 weeks. Outcomes were assessed using the Visual Analogue Scale (VAS), Mayo Wrist Score, range of motion (ROM), grip strength, radiological union, complications, hospital stay and return to activity. Results: The mean Mayo Wrist Score at 24 weeks was significantly higher in the surgical group (88.2 ± 8.1) than in the conservative group (78.4 ± 9.2) (p < 0.001). Excellent-to-good outcomes were achieved in 83.7% of surgical patients versus 54.0% of conservative patients. Surgical patients had lower VAS scores (1.1 ± 0.4 vs 1.8 ± 0.6), greater wrist flexion (74.1° vs 65.2°), better grip strength (88.3% vs 78.5% of normal side), faster radiological union (8.4 vs 9.8 weeks) and earlier return to activities (7.3 vs 10.4 weeks). Overall complication rate was lower in the surgical group (16.2% vs 27.0%), although the surgical group required longer hospitalisation (7.4 vs 2.8 days). Conclusion: Surgical fixation provides superior functional and radiological outcomes compared with conservative management in distal radius fractures, with earlier pain relief, better wrist mechanics and lower mechanical complication rates. Conservative management remains appropriate for stable extra- articular fractures and elderly patients with low functional demands.